2017
DOI: 10.1101/gad.293134.116
|View full text |Cite
|
Sign up to set email alerts
|

High constitutive activity of a broad panel of housekeeping and tissue-specific cis-regulatory elements depends on a subset of ETS proteins

Abstract: Enhancers and promoters that control the transcriptional output of terminally differentiated cells include cell type-specific and broadly active housekeeping elements. Whether the high constitutive activity of these two groups of -regulatory elements relies on entirely distinct or instead also on shared regulators is unknown. By dissecting the-regulatory repertoire of macrophages, we found that the ELF subfamily of ETS proteins selectively bound within 60 base pairs (bp) from the transcription start sites of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 50 publications
1
59
0
Order By: Relevance
“…Cell cultures. Macrophages were derived from bone marrows of C57/BL6 mice (Harlan) as described (Curina et al 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell cultures. Macrophages were derived from bone marrows of C57/BL6 mice (Harlan) as described (Curina et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Table 4). This analysis revealed that: i) constitutive binding of PU.1 (SPI1) was associated with all types of remodeling events; ii) constitutive binding of ELF4 was associated with nucleosome shifts, likely reflecting the high transcriptional activity of ELF4-associated promoters (Curina et al 2017); iii) basal and inducible IRF1 (Interferon Regulatory Factor 1) binding along with inducible IRF3 and STAT2 binding were selectively associated with remodeling events (especially evictions) at the TSS of secondary response genes, which include genes activated in a paracrine/autocrine manner by early released IFNb; iv) inducible NF-kB binding was associated with shifts but not evictions, and this association was stronger for primary than for secondary response gene promoters. The correlation between basal, inducible and reduced TF binding events and nucleosome remodeling at different classes of genes is highlighted in Suppl.…”
Section: Nucleosome Remodeling At Stimulus-regulated Promotersmentioning
confidence: 97%
See 1 more Smart Citation
“…ChIP-seq was carried out using previously described protocols (Curina et al, 2017;Balestrieri et al, 2018) on an Illumina HiSeq 2000 platform. 10 6 (H3K27ac) or 50-150 × 10 6 (TFs) were either fixed with formaldehyde as described before (for H3K27ac, FOXA2, HOXB8, and JUNB ChIP-seq) or fixed with a double cross-linking protocol (for FOS ChIP-seq).…”
Section: Chip-seqmentioning
confidence: 99%
“…Concurrent with the immediate innate immune response, TFEA identified a set of TFs that exhibit a rapid decrease in E-Scores including ELF1/2 [17], TYY1 [30][63], USF1/2 [31], and GABPA [62]. The decreased E-Score set includes TYY1, a transcriptional inhibitor known to be activated directly by NFÎșB [54].…”
Section: Tfea Improves Motif Enrichment Detection By Incorporating Pomentioning
confidence: 99%